Pounder's marine diesel engines and gas turbines - Pounder, C. Coulson (Cuthbert Coulson); Woodyard, D. F. (Douglas F.) (Oxford ; Burlington, MA : Elsevier Butterworth Heinemann, 2004)
Since its first appearance in 1950, Pounder's Marine Diesel Engines has served seagoing engineers, students of the Certificates of Competency examinations and the marine engineering industry throughout the world. Each new edition has noted the changes in engine design and the influence of new technology and economic needs on the marine diesel engine. This eighth edition retains the directness of approach and attention to essential detail that characterized its predecessors. There are new chapters on monitoring control systems and governor systems, gas turbines and safety aspects of engine operation. Important developments such as the latest diesel-electric LNG carriers that will soon be in operation. After experience as a seagoing engineer with the British India Steam Navigation Company, Doug Woodyard held editorial positions with the Institution of Mechanical Engineers and the Institute of Marine Engineers. He subsequently edited The Motor Ship journal for eight years before becoming a freelance editor specializing in shipping, shipbuilding and marine engineering. He is currently technical editor of Seatrade, a contributing editor to Speed at Sea, Shipping World and Shipbuilder and a technical press consultant to Rolls-Royce Commercial Marine. * Designed to reflect the recent changes to SQA/Marine and Coastguard Agency Certificate of Competency exams. Careful organisation of the new edition enables readers to access the information they require * Brand new chapters focus on monitoring control systems and governor systems, gas turbines and safety aspects of engine operation * High quality, clearly labelled illustrations and figures.
Theory and general principles -- Gas-diesel and dual-fuel engines -- Exhaust emissions and control -- Fuels and lubes : chemistry and treatment -- Performance -- Engine and plant selection -- Pressure charging -- Fuel injection -- Low speed engines -- introduction -- MAN B & W low speed engines -- Mitsubishi low speed engines -- Sulzer low speed engines -- Burmeister & Wain low speed engines -- Doxford low speed engines -- MAN low speed engines -- Medium speed engines -- introduction -- Allen (Rolls Royce) -- Alpha Diesel (MAN B & W) -- Caterpillar -- Deutz -- MaK (Caterpillar Motoren) -- MAN B & W Diesel -- Rolls-Royce Bergen -- Ruston (MAN B & W) -- SEMT-Pielstick (MAN B & W) -- Sulzer (Wθartsilθa) -- Wθartsilθa -- Other medium speed engines -- Low speed four-stroke trunk piston engines -- High speed engines -- Gas turbines.
Includes index.
Keywords: Marine diesel motors; Marine gas-turbines.; Electronic books